Early Transjugular Intrahepatic Portosystemic Shunt (TIPS) Placement in Patients with Cirrhosis and Variceal Bleeding - Lang, Min; Fortune, Brett E.; Sands, Mark J.; Bayona-Molano, Maria Del Pilar; Kapoor, Baljendra S. (Digestive Disease Interventions, 2017)
The placement of a transjugular intrahepatic portosystemic shunt (TIPS) has been traditionally used as a rescue treatment for uncontrolled or recurrent acute variceal bleeding (AVB) in patients with cirrhosis. However, more contemporary studies are revealing that early or ‘pre-emptive’ TIPS placement (performed within 24–72 h of AVB presentation) significantly controls bleeding, prevents rebleeding, and improves survival in selected patients when compared with standard pharmacological and endoscopic therapies. Furthermore, the use of early TIPS did not translate to an increased risk of hepatic encephalopathy (HE) for this population. Proper patient selection for early TIPS is paramount, as the procedure is unlikely to benefit patients with advanced decompensated cirrhosis (Child–Turcotte–Pugh [CTP] class C, score > 13) or patients who do not carry high risk with only mild hepatic dysfunction (Child-Turcotte-Pugh class A). Finally, while the current results for early TIPS are promising, further prospective studies are needed to confirm these findings before early TIPS can be widely adopted.
Keywords: early TIPS; variceal bleed; cirrhosis; portal hypertension